PELATIHAN ECOPRINT SEBAGAI ALTERNATIF PROJEK P5 DI SMP NEGERI 3 MALANGBONG GARUT - Satiyasih Rosali, Ely; Darmawan, Darwis; Mulyanie, Erni; RS, Esta Rendra; Muslim, Siska Ryane; Nurlaila, Nurlaila (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Modern education is not solely aimed at enhancing academic knowledge but also plays a crucial role in shaping character and skills that are relevant to future challenges. Within the framework of the Merdeka Curriculum, character development based on Pancasila values through the Student Pancasila Profile Development Project (P5) has become a primary focus. This program aims to create a generation of students who love their country, respect diversity, and actively contribute to sustainable development. One of the approaches to achieving these goals is through activities that creatively and sustainably utilize natural resources. Ecoprint training is a concrete effort to provide students with meaningful and contextual learning experiences while teaching the principles of sustainability. Ecoprint, which uses natural materials such as leaves, flowers, and other plant parts to create artistic patterns on fabric, not only provides students with an economically valuable skill but also fosters environmental awareness. This training not only imparts technical skills but also encourages students to understand the importance of environmental preservation through productive and eco-friendly activities. By integrating this training into the P5 implementation, students are expected to develop entrepreneurial skills that support sustainable development while reinforcing the character traits aligned with the Pancasila Student Profile.